Comenius' ethics: From the heart to the world - Misseri, Lucas Emmanuel (2017)
This paper deals with the ethical views of the 17th century Czech thinker Jan Amos Komenský, also known as Johann Amos Comenius. Comeniologic studies are focused on different aspects of his contribution to education, theology and philosophy but surprisingly there are only a few studies on his ethical standpoints. Jan Patocka classified Comenius's work in three periods: prepansophic, pansophic and panorthotic. Here the focus is on the panorthotic works in order to trace the different conceptions of ethics, virtue and other ethical concepts specially the virtue of prudence (prudentia/phronesis). Furthermore, to have a broader perspective, a short analysis of his prepansophic period book The Labyrinth of the World and the Paradise of the Heart is also included in order to contrast the evolution of the concept of prudence and the ethical sphere in his world-view. The methodology is based on conceptual analysis, the contrast of different references to ethics in his late period books. At the same time, this work is an attempt to extract secular elements for understanding his ethics, although the organic link between philosophy, theology and politics is recognized in his thought.